Derivative-Extended Time Domain Reduction for Coupled Systems Using Chebyshev Expansion - Xiaolong Wang; Yaolin Jiang; Jun Liu (Discrete Dynamics in Nature and Society)
The time domain model reduction based on general orthogonal polynomials has been presented for linear systems. In this paper, we extend this approach by taking the derivative information of the system into account in the context of model reduction of coupled systems. We expand the derivative terms over the Chebyshev polynomial basis and show that Chebyshev coefficients of the expansion possess a specific structure, making it possible to preserve much more time domain information by employing projection methods. Besides, with the well-defined projection matrices, the resulting reduced model shares the same topological structure with the original coupled system. Two numerical examples are simulated to showcase the accuracy of incorporating the derivative information into model reduction.